Impact of Big Data Analytics on Operational Efficiency - Ruli Widyaningtyas,; Sutianingsih,; Ferdian Tomy Pratama,; Nico Irawan, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The goal of this study is to analyze how Big Data Analytics can help improve the efficiency of various industries. It explores how this technology can be used to improve the decision-making process and the allocation of resources. The study additionally highlights the potential of this technology in fields such as healthcare, retail, manufacturing, and supply chain management. The various advantages of Big Data Analytics can be seen in various areas such as improving the efficiency of inventory management and reducing the risk of fraud. However, there are still some challenges that need to be resolved to fully capitalize on its potential. This study provides a variety of practical recommendations to help organizations implement effective BDA strategies. Big Data Analytics can help organizations achieve various operational goals and improve their competitive advantage. It can also help them manage their data more effectively.